2020
DOI: 10.1002/adfm.202005182
|View full text |Cite
|
Sign up to set email alerts
|

Mimic Drug Dosage Modulation for Neuroplasticity Based on Charge‐Trap Layered Electronics

Abstract: The human brain is often likened to an incredibly complex and intricate computer, rather than electrical devices, consisting of billions of neuronal cells connected by synapses. Different brain circuits are responsible for coordinating and performing specific functions. The reward pathway of the synaptic plasticity in the brain is strongly related to the features of both drug addiction and relief. In the current study, a synaptic device based on layered hafnium disulfide (HfS2) is developed for the first time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…2(d) which is four orders of magnitude faster than the instantaneous information transmission in the biological synapses (typically 50 ms) 58 . Possible reasons for the ultrashort optical pulse detection capability are ultrafast optical signal propagation speed 2,35,39,59 and ultrasensitive optical detection 60 based on the polycrystalline MoS 2 films. As a result, our synaptic transistors could improve the recognition rate of single optical pulse significantly and achieve an ultralow power consumption of 40 aJ, two orders of magnitude lower than that of biological synapses.…”
Section: Ids − Idarkmentioning
confidence: 99%
See 4 more Smart Citations
“…2(d) which is four orders of magnitude faster than the instantaneous information transmission in the biological synapses (typically 50 ms) 58 . Possible reasons for the ultrashort optical pulse detection capability are ultrafast optical signal propagation speed 2,35,39,59 and ultrasensitive optical detection 60 based on the polycrystalline MoS 2 films. As a result, our synaptic transistors could improve the recognition rate of single optical pulse significantly and achieve an ultralow power consumption of 40 aJ, two orders of magnitude lower than that of biological synapses.…”
Section: Ids − Idarkmentioning
confidence: 99%
“…Yoo's group 37 has confirmed that the MoS 2 layer could act as a high-efficiency charge-trapping layer via control experiment. Although the two-terminal devices are easier to form a crossbar-array structure, the inhibitory synaptic behaviours cannot be achieved in these devices 39 . Furthermore, three-terminal gate-control synaptic transistors are able to possess another degree-of-freedom to modulate the neuromorphic function apart from optical modulation 8,40 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations